Hyperfine interaction in cobalt by high-resolution neutron spectroscopy. (5th December 2018) - Chatterji, Tapan; Zamponi, Michaela; Wuttke, Joachim
Abstract: We have investigated the ferromagnetic phase transition of elemental Co by high-resolution neutron backscattering spectroscopy. We monitored the splitting of the nuclear levels by the hyperfine field at the Co nucleus. The energy of this hyperfine splitting is identified as the order parameter of the ferromagnetic phase transition. By measuring the temperature dependence of the energy we determined the critical exponent and the ferromagnetic Curie temperature of K. The present result of the critical exponent agrees better with the predicted value (0.367) of the three-dimensional Heisenberg model than that determined previously by nuclear magnetic resonance.